Synthesis and modification of poly(ethyl 2-(imidazol-1-yl)acrylate) (PEImA). (3rd October 2017) - Rössel, C.; Billing, M.; Görls, H.; Festag, G.; Grube, M.; Bellstedt, P.; Nischang, I.; Schacher, F.H.
Abstract: We present the synthesis and characterization of poly(ethyl 2-(imidazol-1-yl)acrylate) (PEImA) using free radical polymerization in various solvents with and without acids as additive. In addition, PEImA was also prepared using anionic polymerization with KO t Bu as initiator in DMF and in THF at different M:I ratios. The resulting polymers of moderate dispersity were characterized by 1 H-NMR, solid state 13 C-NMR, and size exclusion chromatography (SEC) both in water and DMAc. PEImA is an interesting highly substituted polymer as it can be modified by methylation to poly(ethyl 2-(methyl imidazolium-1-yl iodide)acrylate) PEMeImA, via ester cleavage into the polyzwitterion poly(2-(imidazol-1-yl)acrylic acid) (PImAA), and – finally - to poly(2-(methyl imidazolium-1-yl)acrylic acid) (PMeImAA) if both modification steps are carried out. We also investigated structure and solubility of these different polyelectrolytes using potentiometric titration in aqueous media. Graphical abstract: Highlights: We report on the synthesis of Poly(ethyl 2-(imidazol-1-yl)acrylate) (PEImA). PEImA can be prepared using either free radical or anionic polymerization. PEImA can further be transformed into different polyampholytes or polyzwitterions.